(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2015)
This contribution aims to investigate the initial rows of the attic decree on weights and measures dating from the end of the second century B.C. (IG II2 1013). The analysis mainly focuses on the integrations proposed in some of the editions of the ψήφισμα and will try to verify their plausibility from the juridical viewpoint of legal history. Particular attention is dedicated to the reconstruction of the lost lines of the decree, to the application of the ἀπαγωγή against those who act fraudulently in connection with weights and measures on the marketplace, and to the various sanctions directed towards free individuals as well as slaves. Il contributo è volto all’indagine delle prime linee del decreto attico sui pesi e misure della fine del II secolo a.C. (IG II2 1013). L’analisi si incentra in particolare sulle integrazioni proposte in alcune edizioni dello ψήφισμα ed è tesa a verificarne la loro accoglibilità sotto il profilo giuridico. Una particolare attenzione è posta alla ricostruzione delle linee non conservate del decreto, all’effettivo ricorso all’ἀπαγωγή contro colui che abbia tenuto nel mercato una condotta fraudolenta nel peso e nelle misura, alle diverse sanzioni previste nei confronti dei liberi e degli schiavi.